Effect of feeding coriander (Coriandrum sativum, L.) on egg production performance and nutrient retention in laying Japanese quails - Guler, T.; Ertas, O. N.; Ciftci, M.; Dalkilic, B. (Taylor & Francis Ltd, 2006)
The effect of coriander seeds on egg production performance and nutrient retention was investigated in laying Japanese quails. A total of 375 birds (42 d) were randomly and equally divided into five treatment groups: 0, 0.5, 1, 2 or 4% ground coriander seeds were added to rations of respective groups. The feed intake of the birds fed on diets containing coriander seeds was higher than control diet (P < 0.05). Egg production was similar in all groups. The highest egg weight, yolk weight, albumen weight, Hough units, retention of nutrients and the best feed efficiency were recorded in 1% and 2% coriander groups (P < 0.05). Other parameters were not affected by coriander supplementation. Use of 1-2% coriander seeds for laying quails ration is recommended.
Keywords: coriander seed; egg; digestibility; layers; Japanese quail